Adolescent Pregnancy in Indonesia Leads to Severe Psychological Impact: Kehamilan Remaja di Indonesia Menimbulkan Dampak Psikologis yang Parah - Arni Azis Yuliyantiningsih; Nurul Azizah (Academia Open, 2024)
Adolescents are particularly vulnerable to unwanted pregnancies, leading to significant psychological impacts. This study explores the psychological effects of pregnancy on 15-18-year-old adolescents, focusing on a 17-year-old case study. Using in-depth interviews and the DASS 42 scale, we found that pregnancy in adolescents leads to depression, anxiety, and stress, affecting both the individual and their environment. The subject experienced familial neglect and initial denial, attempted to terminate the pregnancy, but ultimately accepted it with family and partner support. The findings highlight the need for robust support systems and preventive education to address adolescent pregnancy's psychological challenges. Highlight: Adolescent pregnancy causes severe depression, anxiety, and stress. Family and partner support is crucial for coping. Preventive education is essential for reducing psychological distress. Keyword: dolescent pregnancy, psychological impact, depression, anxiety, stress